German nursing study programs from the students' perspective: First results of a nationwide longitudinal study - Großmann, Daniel; Olden, Daria; Dorin, Lena; Meng, Michael; Peters, Miriam; Reuschenbach, Bernd (Pflege, 2023)
German nursing study programs from the students' perspective: First results of a nationwide longitudinal study The Nursing Professions Act establishes a concrete framework for academic nursing education in Germany for the first time. The primary qualifying nursing courses started in 2020 and will be accompanied by a systematic reporting of students' experiences over a period of three years. The article presents the results of the initial survey period (2021) on the students' point of view. Challenges and the need for further regulation of the primary qualifying nursing studies are analyzed and approaches to solutions are developed. The online survey is designed as a longitudinal cohort study with three measurement periods (2021, 2022, 2023). A descriptive analysis considers data of = 57 students in the initial survey period. The primary qualifying nursing study program is rated good overall (overall grade 2.32). However, one third (35.85%) are more critical in their assessments. Every second student perceives a need for adjustment in the financing of students. Learning in clinical placement settings often does not meet students' expectations. 86% of respondents report that nursing practice sites are insufficiently informed about students' qualification. Students' financing, and in particular the payment of assignments in the nursing practice, represents a regulatory gap with need for short-term solutions. For learning in nursing practice, there is a need for an enhanced practical placement guidance that is better geared to academic nursing education. This is accompanied by the need for a more specific definition of later professional fields and job profiles.